Markets wanted: Expectation overshooting in transition - Frank Neher (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2011)
We analyse and compare individual beliefs about the effects of competition and their evolution over time in transition economies and experienced market economies. At the onset of transition, competition beliefs in transition countries are far more positive than in market economies. Over time, this difference has vanishes. Convergence can be attributed to changing believes in transition countries. We argue that overly optimistic competition beliefs in transition countries contributed to the possibility of implementing far reaching pro-market reforms and show that competition beliefs underlay support for economic reform. The empirical analysis is supplemented with a simple learning model rationalizing the findings on competition belief overshooting.
Keywords: D72; D83; P5; 330; convergence; beliefs; public support; reform; bias; signalling